1996
DOI: 10.1097/00019606-199612000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Specimen Stability for DNA-based Diagnostic Testing

Abstract: The use of molecular diagnostic testing is increasing in the clinical setting; therefore, data regarding DNA stability in clinical specimens are essential for correct test performance and interpretation. This study was designed to determine DNA stability in peripheral blood and solid tissue under different storage conditions. DNA quality and yield were assayed by spectrophotometric absorbance, gel electrophoresis, and suitability for Southern hybridization and polymerase chain reaction (PCR), the most widely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In addition to using laboratory resources more efficiently, such batching eliminates run-to-run variations in a PCR which might complicate interpretation of results. Several groups have reported that viral DNA stored for extended periods generally remains positive by qualitative PCR (2,3,8). However, it has not been investigated whether standard storage conditions retain the quantitative information on the viral DNA present in patient specimens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to using laboratory resources more efficiently, such batching eliminates run-to-run variations in a PCR which might complicate interpretation of results. Several groups have reported that viral DNA stored for extended periods generally remains positive by qualitative PCR (2,3,8). However, it has not been investigated whether standard storage conditions retain the quantitative information on the viral DNA present in patient specimens.…”
mentioning
confidence: 99%
“…Wiedbrauk and Cunningham (8) showed that HSV DNA can be amplified from cerebrospinal fluid specimens stored at temperatures ranging from 23 to Ϫ72°C over a period of 30 days. Farkas et al (2) used purified DNA stored at 4°C for 3 years to successfully amplify the gene for factor V. However, the same group suggested that frozen swab specimens should be tested within 60 days (3). An important distinction of these earlier studies is that none used real-time detection of the PCR product, relying instead on less-sensitive qualitative detection by ethidium bromide staining of agarose gels.…”
mentioning
confidence: 99%
“…DNA extraction and polymerase chain reaction (PCR) amplification were carried out using standard techniques 6 . DNA samples from the families underwent PCR with the fluorescently labelled microsatellite marker D1S2868 (Applied Biosystems PRISM linkage mapping set version 2) and two fluorescently labelled oligonucleotide primers (designed in‐house, and synthesized by Invitrogen TM Life Technologies; available on request) from the region of chromosome 1p21‐22.…”
Section: Methodsmentioning
confidence: 99%
“…In our experience, once the infrastructure and physician network were built and personnel were trained, then the attention could be focused on the expansion of the collection to other tissue types (eg, preneoplastic lesions and inflammatory tissues) and biological materials (eg, blood, saliva, serum, plasma, and urine). Since the newest molecular techniques require the availability of adequate amounts of high-quality specimens, 15,16 standardized SOPs for the accrual, processing, and storage of tissues had to be established. One of the most important outcomes of the NCI-funded Partnership between PSMHS and MCC is that it allowed the implementation of biobank-related guidelines already proved to be effective at MCC, and the training of staff in tissue biobanking by MCC co-leaders with that expertise.…”
Section: Flores Et Almentioning
confidence: 99%